PELAKSANAAN MANAJEMEN APARATUR PEMERINTAH - Rosalia, Yunita (Universitas Riau, 2016)
Implementation Government Personnel Management. This study aims to investigatethe implementation of government personnel management at the City District Office TembilahanIndragiri Hilir. The data used in this study are primary and secondary data. The data is compiledfrom observations and interviews with officials at the City District Office Tembilahan Indragiri Hilirwith the duties and functions of the City District Office Tembilahan Indragiri Hilir. Technical analysisin this research is qualitative data that has been obtained in the study were collected, then groupedto serve as an input to be used as evidence in the implementation of scientific writing. Furtherconfirmation of the other informants conducted to obtain valid data. Once the data is processed,further discussion of the qualitative data in the form of descriptive analyzes carefully. Data analysiswas performed inductively, that analysis by drawing conclusions on the data collected from thegeneral form or reasoning to reach conclusions about all the elements - elements that do not studyexamined / investigated. The results showed that the implementation of government personnelmanagement at Head Office Tembilahan City has basically been running well but not fully achievedas objectives. It can be seen from the Head of the management planning apparatus or its staff, thelevel of understanding of the duties and functions of the apparatus in accordance with applicableregulations, the level of sensitivity of job duties with the results achieved, and the priority of thetasks and urgent work and consistency between the tasks and functions of each - each section withthe activities carried out by the Head Office of the City Tembilahan.